Prior hospitalizations as a predictor of prognosis in heart failure with mildly reduced ejection fraction - Steffen, Henning Johann; Behnes, Michael; Schmitt, Alexander; Abel, Noah; Lau, Felix; Reinhardt, Marielen; Akin, Muharrem; Bertsch, Thomas; Ayoub, Mohamed; Mashayekhi, Kambis; Weidner, Kathrin; Akın, Ibrahim; et al. (Clinical research in cardiology, 2025)
Objective This study aims to investigate the prognostic impact of the presence and type of prior hospitalizations in patients with heart failure with mildly reduced ejection fraction (HFmrEF). Background Data investigating the prognostic impact of the present and type of previous all-cause hospitalizations in HFmrEF is limited. Methods Consecutive patients hospitalized with HFmrEF at a single medical center were retrospectively included from 2016 to 2022. The prognosis of patients with a prior hospitalization < 12 months was compared to patients without. The primary endpoint was all-cause mortality at 30 months (median follow-up), the key secondary endpoint was heart failure (HF)-related rehospitalization at 30 months. Results Two thousand one hundred eighty four patients with HFmrEF were included, 34.8% had a previous hospitalization < 12 months (admission to internal medicine and geriatrics: 60.8%, surgical department: 23.5%). The presence of a previous hospitalization was associated with an increased risk of all-cause mortality (38.6% vs. 27.4%; HR = 1.51; 95% CI 1.30-1.76; p = 0.01) and HF-related rehospitalization at 30 months (21.2% vs. 9.1%; HR = 2.48; 95% CI 1.96-3.14; p = 0.01), even after multivariable adjustments. However, the department of previous hospitalization (internal medicine vs. surgical) did not significantly affect the risk of 30-months all-cause mortality (37.1% vs. 43.2%; HR = 0.82, 95% CI 0.63-1.08; p = 0.16) or HF-related rehospitalization (24.0% vs. 16.8%; HR = 1.47, 95% CI 0.98-2.24; p = 0.07). Finally, the type of previous admission (i.e., elective, emergency vs. HF-related admission) (log-rank p = 0.29) did not affect the risk of 30-months all-cause mortality. Conclusion Prior hospitalizations within 12 months were independently associated with impaired long-term mortality in patients with HFmrEF, irrespective of the department or type of prior admission.